2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610202
|View full text |Cite
|
Sign up to set email alerts
|

A new concept for noninvasive tinnitus treatment utilizing multimodal pathways

Abstract: -Current noninvasive treatments for tinnitus have shown mixed results. There have been encouraging developments in using invasive brain or vagal nerve stimulation to modulate neural populations driving the tinnitus percept. However, these invasive treatments can only be used in a small patient population with severe conditions. In this preliminary study, we present a new treatment option we call Multimodal Synchronization Therapy (MST), which attempts to achieve synchronized and localized brain activation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Bi‐modal stimulation is emerging as a compelling approach to tinnitus treatment . De Ridder et al paired tones with VNS in 10 tinnitus patients who were previously unresponsive to other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Bi‐modal stimulation is emerging as a compelling approach to tinnitus treatment . De Ridder et al paired tones with VNS in 10 tinnitus patients who were previously unresponsive to other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The overall ndings from this TENT-A2 study indicate that a diverse range of electrical and sound stimulus combinations can signi cantly improve tinnitus symptoms and aligns with ndings from previous animal and human research on bimodal neuromodulation. [7][8][9][10][11][12][13][14][15][16] Animal studies have shown that sound stimulation paired with electrical stimulation of different body locations (or related nerves), such as the face, neck, ear, tongue, back and limbs can all drive extensive neural plasticity across the auditory pathway, including in the cochlear nucleus, inferior colliculus and auditory cortex. 7,8,10,13−16 Both pure tone bursts and wideband noise bursts can be effective at driving signi cant auditory plasticity with bimodal neuromodulation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Encouragingly, there has been a recent convergence of ndings across multiple animal and human studies demonstrating that bimodal neuromodulation combining sound with electrical stimulation of peripheral nerves, including vagus, trigeminal and other somatosensory nerves, can drive neural plasticity relevant for tinnitus treatment and signi cantly improve tinnitus symptoms. [7][8][9][10][11][12][13][14][15][16] Previous animal studies have shown that bimodal stimulation combining electrical body stimulation combined with pure tones or wideband noise can alter brain activity within auditory regions associated with tinnitus. 7,8,13−15 These studies demonstrated that electrical stimulation of the vagus or trigeminal nerves or the surface of different body regions in animals (e.g., tongue, face, neck and ear) can alter brain patterns relevant for tinnitus treatment and reduce tinnitus symptom severity in human patients.…”
Section: Introductionmentioning
confidence: 99%
“…At present, cochlear implantation is not applicable to tinnitus sufferers with normal hearing. The present strategy can be combined with other forms of treatment such as cognitive training and coordinated stimulation to produce a long-lasting effect and eventually find a cure for tinnitus (Cima et al., 2012; Engineer et al., 2011; Gloeckner, Smith, Markovitz, & Lim, 2013; Marks et al., 2018; Tass, Adamchic, Freund, von Stackelberg, & Hauptmann, 2012).…”
Section: Discussionmentioning
confidence: 99%